2015
DOI: 10.1001/jamainternmed.2015.2081
|View full text |Cite
|
Sign up to set email alerts
|

Use of Preoperative Testing and Physicians’ Response to Professional Society Guidance

Abstract: The value of routine preoperative testing before most surgical procedures is widely considered to be low. To improve the quality of preoperative care and reduce waste, 2 professional societies released guidance on use of routine preoperative testing in 2002, but researchers and policymakers remain concerned about the health and cost burden of low-value care in the preoperative setting.OBJECTIVE To examine the long-term national effect of the 2002 professional guidance from the American College of Cardiology/Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 28 publications
1
36
0
1
Order By: Relevance
“…Both are crucial when trying to assess the impact of an educational program. 15 , 16 Without an adequate control group and a method that accounts for the change in knowledge over time for other reasons, any observed findings might be due to unmeasured confounding factors. In our study, the inclusion of this control group was important since we expected that knowledge related to antimicrobial prescribing might increase over the course of an internal medicine rotation, even without access to an app.…”
Section: Discussionmentioning
confidence: 99%
“…Both are crucial when trying to assess the impact of an educational program. 15 , 16 Without an adequate control group and a method that accounts for the change in knowledge over time for other reasons, any observed findings might be due to unmeasured confounding factors. In our study, the inclusion of this control group was important since we expected that knowledge related to antimicrobial prescribing might increase over the course of an internal medicine rotation, even without access to an app.…”
Section: Discussionmentioning
confidence: 99%
“…(15) We used visit diagnoses and reasons for visit from our prior work to identify patients with other risk factors for adverse cardiovascular events, including hypertension, dyslipidemia, cigarette smoking, obesity, diabetes, chronic kidney disease, chronic obstructive pulmonary disease, CAD, and stroke (16,17). We were unable to validate our PAD diagnosis codes but they were extracted from an American Heart Association Scientific Statement, and the NAMCS/NHAMCS uses rigorous methods to review and classify data reported on Patient Record Forms.…”
Section: Methodsmentioning
confidence: 99%
“…5 Despite strong evidence that performing diagnostic testing such as laboratory tests, electrocardiograms (EKG) and chest x-rays provide limited benefit in routine preoperative care, this practice remains widespread. 6 …”
Section: Introductionmentioning
confidence: 99%